Multi-Sensor System for Underwater Pothole Detection to Enhance Road Safety During Monsoon Seasons - Jashanpreet Singh; Gaurav; Harshit; Jacob Chacko (International Journal of Mechanical Dynamics and Systems Analysis, 2026)
Monsoon seasons across India and similar tropical regions severely compromise road safety by causing water accumulation that conceals dangerous potholes beneath stagnant pools, leading to frequent vehicle damage, tire punctures, and fatal accidents. Traditional detection methods relying on smartphone accelerometers, ultrasonic sensors, or machine vision fail under flooded conditions due to acoustic signal reflection at water surfaces and optical distortions from glare and turbidity. This research proposes an innovative multi-sensor fusion system that integrates a low-cost HC-SR04 ultrasonic sensor for dry pothole detection with a 405 nm blue laser diode structured-light module for underwater pothole profiling, enabling comprehensive road hazard identification regardless of surface wetness.The ultrasonic sensor continuously measures road-to-sensor distance via time-of-flight, flagging sudden depth variations exceeding 3 cm as dry potholes. Complementarily, the blue laser projects a thin line pattern across the road surface, which a co-aligned CMOS camera captures to reveal submerged topography through laser line deformation analysis. Custom image processing algorithms—employing grayscale conversion, Gaussian noise filtering, Sobel edge detection, and Hough transform line fitting—extract pothole depth and width from the distorted laser profile using calibrated camera-laser triangulation geometry. An Arduino Uno microcontroller orchestrates real-time sensor polling, preliminary decision logic (Boolean OR fusion of ultrasonic and optical flags), debounce filtering, and driver alerts via multi-color LEDs and variable-tone buzzer.Theoretical simulations based on sensor datasheets and optical propagation models predict >90% detection accuracy for potholes 3-15 cm deep in water depths up to 10 cm, with end-to-end latency under 200 ms suitable for vehicular applications. Total prototype cost remains below ₹7000, making deployment feasible across budget-constrained municipalities. This embedded solution bridges critical gaps in existing technologies and establishes a scalable foundation for monsoon-resilient intelligent transportation systems in developing regions.
Keywords: Arduino Microcontroller; Underwater pothole detection; blue laser structured light; embedded real-time processing; image processing algorithms; monsoon road safety; sensor fusion; ultrasonic ranging